Virtual Learning and Memory Dissonance - Ismail, Nyak Mutia; Sabrina, Sabrina (Jurnal Ilmiah Peuradeun, 2023)
This study aimed to find out declarative memory recalls during online classes. Using a qualitative approach, the instruments used were simple and difficult word-sets. The data were collected through Zoom and WhatsApp platforms and later analyzed using interactive analysis. The results revealed two dissonances encountered: Informational Loss and Built-Up Dissonance. Initially, in the simple-word set, the majority of the students encountered Informational Loss 74 times (after 30 seconds) increasing to 97 times (after 30 minutes). In difficult word sets, it occurred 144 times, increasing to 154 times within identical spans. Regarding Built-Up Dissonance, it occurred 19 times (after 30 seconds), decreasing to 13 times (after 30 minutes) in simple word sets, and 27 times (after 30 seconds), increasing to 30 times (after 30 minutes) in difficult word sets. Surprisingly, it was found that in the recall test, linguistic buffering was generally employed instead of visual buffering. This finding helps teachers understand that virtual learning prompts need to be accompanied by activities involving procedural memory to minimize dissonances.